Biologically Inspired Synthesis Route to Three-Dimensionally Structured Inorganic Thin Films. (9th January 2008) - Schwenzer, Birgit; Morse, Daniel E.
Abstract : Inorganic thin films (hydroxide, oxide, and phosphate materials) that are textured on a submicron scale have been prepared from aqueous metal salt solutions at room temperature using vapor-diffusion catalysis. This generic synthesis approach mimics the essential advantages of the catalytic and structure-directing mechanisms observed for the formation of silica skeletons of marine sponges. Chemical composition, crystallinity, and the three-dimensional morphology of films prepared by this method are extremely sensitive to changes in the synthesis conditions, such as concentrations, reaction times, and the presence and nature of substrate materials. Focusing on different materials systems, the reaction mechanism for the formation of these thin films and the influence of different reaction parameters on the product are explained.